2018
DOI: 10.1080/10428194.2018.1542152
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Behcet’s-like disease with myelodysplastic neoplasms with trisomy 8: a French case series and literature review

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…MDS-vasculitis patients are generally younger with a prevalence of male sex, as compared to MDS without vasculitis [68]. No correlations with specific MDS subtypes have been reported [69], except for Behçet's-like syndrome and trisomy 8 [70]. Regarding vasculitis subtypes, the most common are polyarteritis nodosa and giant-cell arteritis.…”
Section: Aid In Mdsmentioning
confidence: 98%
See 2 more Smart Citations
“…MDS-vasculitis patients are generally younger with a prevalence of male sex, as compared to MDS without vasculitis [68]. No correlations with specific MDS subtypes have been reported [69], except for Behçet's-like syndrome and trisomy 8 [70]. Regarding vasculitis subtypes, the most common are polyarteritis nodosa and giant-cell arteritis.…”
Section: Aid In Mdsmentioning
confidence: 98%
“…The latter displays a milder clinical course compared to the idiopathic form (less frequent headaches, jaw claudication and optic neuropathy). Moreover, MDS-associated Behçet's-like syndrome has a delayed onset, greater gastrointestinal and oral involvement and reduced ocular manifestations than the idiopathic form [70,71]. Other frequent associations are relapsing polychondritis and SLE, whilst SS, RA, polymyalgia rheumatica, uveitis, pulmonary proteinosis, thyroiditis, and myositis are sporadically reported [50,68,94].…”
Section: Aid In Mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between phenotype and genotype have been recently identified within SIADs that are associated with MDS. Wesner et al reported a French retrospective caseseries with a literature review of 39 patients with Behçet's-like syndrome associated with trisomy-8 positive MDS, characterized by orogenital aphtosis, skin features and severe ulcerative digestive disease of ileocecal distribution [55]. Other clinical manifestations of Behçet's disease, such as arthritis or neutrophilic dermatosis, have also been described in MDS patients with trisomy 8, with the exception of ocular and neurologic manifestations that are usually absent.…”
Section: Characteristics Of the Underlying Mdsmentioning
confidence: 99%
“…Until now, however, no paper has reported hematologic involvement as a particular phenotype in BS, and there has been little research on hematologic involvement in large BS samples. Some studies have even referred to it as a "Behçet-like disease" [19,20]. Analyses of several case reports have shown an association between trisomy 8 and intestinal BD with MDS [2,3,21,22].…”
Section: Discussionmentioning
confidence: 99%